Nanofiber Cellulose Cocoa’s Hardboard on Compression Strength and Termite Resistance - Hendrian Budi Bagus Kuncoro; Zulmahdi Darwis; Amelia Rizqiyanti (Applied Research on Civil Engineering and Environment (ARCEE), 2022)
Each year’s use of wood needs increases, but the resulting wood production is not in proportion to meet that need. The effort is required to overcome this by using a wood substitute that includes wood-based fiberboard. The manufacture of fiberboards requires a chemical base for adhesive, which can be used to reduce the use of chemicals and thus be used in the cacao fruit’s nanofibers. Related to wood materials, the natural enemy most damaging of these materials is termites. Termites are wood-eating insects that can reduce the quality of timber, for handling this a curing process can be employed using a sourced leaf with an antifeedant. The purpose of this study is to identify the compression failure and resilience of the fiberboard termites after being given an extract of cocoa skin and soursop leaves. Dimension of compression specimens is 200 mm x 50 mm x 30, compression perpendicular is 150 mm x 50 mm x 30 mm and terminate resistence is  70 mm x 50 mm x 150 mm with hollow’s diametres 2 mm deep 1 cm. The standard that used to measure compression is SNI 03-3958-1995 and termite resistance of hardboard is SNI SNI 01-7207-2006. The extra variety used is 0%, 10%, 15%, 20% and 25%. Each variation will be done with a compression failure and termite resistance. Three different test items will be made with a total of 30 test items. Research shows compression failure parallel in strong class V wood, while compression failure perpendicular is included in the E5 quality code. Termite resistance 0%, 10% and 15% include C level damage while at 20% and 25% variation, including B damage.